Analisis Kebutuhan dan Strategi Penggunaan Teknologi Tepat Guna Untuk Pengembangan Usaha Kuliner (Studi Kasus: UMKM Sego Ceker TKMP) - Rafeyfa Asyla Arianti; Rachmasari Pramita Wardhani; Lukman; Septina Rana Aqillah; Rezky Gunawan; Rifvo Putra Herlambang (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2026)
The existence of technology in its implementation to run a business needs to be a priority, in terms of running its business. Often there are obstacles or deficiencies that need to be addressed, MSME Sego Ceker TKMP is a business in the culinary field located in a fairly strategic position, in the city of Balikpapan. This culinary is quite popular with the community, especially students becauseof its affordable prices and diverse menus. Therefore, for business development,it is necessary to identify the use of technology and analyze technological needs that support the increase in the effectiveness and efficiency of the Sego Ceker TKMP business operations. The method used is a qualitative approach, namely interview techniques and analyzed based on location aspects, market and marketing aspects, operational technical aspects and strategic analysis with the SWOT method. It is hoped that this research can be a reference for decisionmaking in determining policies for the development of the MSME Sego Ceker TKMP business.